2020
DOI: 10.1038/s41559-020-1216-4
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of multiple stressors on freshwater biota across spatial scales and ecosystems

Abstract: Climate and land-use change drive a suite of stressors that shape ecosystems and interact to yield complex ecological responses, i.e. additive, antagonistic and synergistic effects.Currently we know little about the spatial scale relevant for the outcome of such interactions and about effect sizes. This knowledge gap needs to be filled to underpin future land management decisions or climate mitigation interventions, for protecting and restoring freshwater ecosystems. The study combines data across scales from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
264
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 454 publications
(308 citation statements)
references
References 50 publications
12
264
1
1
Order By: Relevance
“…As we found no collinearity between chemical pollution and other pressures (Supplementary Information-Section 8), our analyses (visual inspection of the raw data plots and the statistical tests) clearly point to mixture exposures acting as a significant limitation to maintain or reach high or good ecological status. The msPAF-metric can be used as pollution pressure metric in a comprehensive multiple-stress assessment in applied ecology, as it is quantitative in kind, and as it relates to impact magnitudes (this study) 4,15 .…”
Section: (4) Does Chemical Pollution Act As Factor That Limits Maintamentioning
confidence: 99%
See 1 more Smart Citation
“…As we found no collinearity between chemical pollution and other pressures (Supplementary Information-Section 8), our analyses (visual inspection of the raw data plots and the statistical tests) clearly point to mixture exposures acting as a significant limitation to maintain or reach high or good ecological status. The msPAF-metric can be used as pollution pressure metric in a comprehensive multiple-stress assessment in applied ecology, as it is quantitative in kind, and as it relates to impact magnitudes (this study) 4,15 .…”
Section: (4) Does Chemical Pollution Act As Factor That Limits Maintamentioning
confidence: 99%
“…The latter figure is most closely related to the impact-related principle of the ecological status (Supplementary Information-Section 1). The HI Median-EC50 -metric for chemical pollution appears to deliver relevant, quantitative information on the expected magnitude of possible impacts, so that it can be used as pollution pressure metric in a comprehensive multiple stress assessment in applied ecology 4,15,44 .…”
mentioning
confidence: 99%
“…In concert, multiple anthropogenic pressures-modified by aquatic processing-(potentially) threaten the ecological status of surface waters (EEA 2018). Disentangling and quantifying the cause-and-effect relationship between multiple pressures and ecological functioning is challenging, especially when addressing the regional scale (Birk et al 2020). To understand effects of land use on water quality, we need (i) monitoring, (ii) modelling, (iii) experiments and (iv) expert judgement.…”
Section: Future Pathways and Recommendations For A Sustainable Bioecomentioning
confidence: 99%
“…Recent comparative studies have found that populations experiencing high levels of anthropogenic stress are likely to occur in regions also subjected to especially high exposure to climate change [5,9]. This convergence of stressors can interact synergistically or antagonistically [10], which makes their combined effects difficult to predict. Thus, despite the clear need to assess co-occurring threats, doing so is challenging because it requires substantial data as well as complex and sophisticated models [11].…”
Section: Introductionmentioning
confidence: 99%